2013
DOI: 10.1186/1129-2377-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of migraine and co-morbid psychiatric disorders among students of Cumhuriyet University

Abstract: BackroundThe aim of this study was to investigate the prevalence of migraine and associated psychiatric disorders among university students at Cumhuriyet University of Sivas in Turkey.MethodsA total of 1601 university students participated in this study and answered the questionnaires. The study was conducted in three stages: the self-questionnaire, the neurological evaluation, and the psychiatric evaluation. In the first stage, the subjects completed a questionnaire to assess migraine symptoms. In the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
21
0
2
Order By: Relevance
“…Likewise, comorbid BD was reported to be the second most prevalent comorbid psychiatric disorder in migraineurs as preceded by major depressive disorder 14. Other studies addressing the prevalence of BD among migraineurs indicated twofold increase in BD in patients with migraine than in those without migraine,17 while BD was reported only in 1.2%–1.3% of migraineurs in these studies 17,18. A family history of BD, type I BD in particular, was more common in migraineurs with comorbid BD than in those without comorbid BD in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…Likewise, comorbid BD was reported to be the second most prevalent comorbid psychiatric disorder in migraineurs as preceded by major depressive disorder 14. Other studies addressing the prevalence of BD among migraineurs indicated twofold increase in BD in patients with migraine than in those without migraine,17 while BD was reported only in 1.2%–1.3% of migraineurs in these studies 17,18. A family history of BD, type I BD in particular, was more common in migraineurs with comorbid BD than in those without comorbid BD in our cohort.…”
Section: Discussionmentioning
confidence: 74%
“…In all, 295 articles were eliminated from our analysis: 35 were duplicates, two letters, 11 reviews, 165 articles describing the genetics, diagnosis and treatment of headache, 78 studies analysing adolescent participants and four analysing the adult population. Finally, 56 articles incorporating 34 904 individuals were included in this paper (Fig. , Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past 20 years, the prevalence of migraine in university students from various academic backgrounds in different countries has been evaluated using a variety of methods, including face‐to‐face interviews and questionnaires . This variation in methodology has created a substantial inconsistency in the findings between studies, with migraine prevalence ranging from 2.4% to 48.5% .…”
Section: Introductionmentioning
confidence: 99%
“…The results were in line with the findings of other studies in this field. [17][18][19][20] The incidence of migraine is 6.9% and in the other Iranian research conducted on students, migraine incidence is reported as 7.14%. On the contrary, in a research conducted in India (2013) on medical students, migraine incidence was 44% 21 and in The U.S. (2014) it was reported as 24% 22 that can result from geographic and racial differences.…”
Section: Discussionmentioning
confidence: 99%